Quantification of Förster resonance energy transfer by monitoring sensitized emission in living plant cells - Müller, Sara M.; Galliardt, Helena; Schneider, Jessica; Barisas, B. G.; Seidel, Thorsten (Frontiers in Plant Science, 2013)
Förster resonance energy transfer (FRET) describes excitation energy exchange between two adjacent molecules typically in distances ranging from 2 to 10 nm. The process depends on dipole-dipole coupling of the molecules and its probability of occurrence cannot be proven directly. Mostly, fluorescence is employed for quantification as it represents a concurring process of relaxation of the excited singulet state S1 so that the probability of fluorescence decreases as the probability of FRET increases. This reflects closer proximity of the molecules or an orientation of donor and acceptor transition dipoles that facilitates FRET. Monitoring sensitized emission by 3-Filter-FRET allows for fast image acquisition and is suitable for quantifying FRET in dynamic systems such as living cells. In recent years, several calibration protocols were established to overcome previous difficulties in measuring FRET-efficiencies. Thus, we can now obtain by 3-filter FRET FRET-efficiencies that are comparable to results from sophisticated fluorescence lifetime measurements. With the discovery of fluorescent proteins and their improvement towards spectral variants and usability in plant cells, the tool box for in vivo FRET-analyses in plant cells was provided and FRET became applicable for the in vivo detection of protein-protein interactions and for monitoring conformational dynamics. The latter opened the door towards a multitude of FRET-sensors such as the widely applied Ca2+-sensor Cameleon. Recently, FRET-couples of two fluorescent proteins were supplemented by additional fluorescent proteins towards FRET-cascades in order to monitor more complex arrangements. Novel FRET-couples involving switchable fluorescent proteins promise increase the utility of FRET through combination with photoactivation-based super-resolution microscopy.